Analisis Potensi Energi Listrik pada Hybrid Renewable Energy System (HRES) Berbasis Surya dan Angin - Muhamad Fahmi Amrillah; Eko Nugroho Widjatmoko; Lia Kamelia (CYCLOTRON, 2026)
The increasing electricity demand in Indonesia encourages the development of sustainable and environmentally friendly renewable energy sources. This study aims to analyze the electrical energy potential of a solar–wind-based Hybrid Renewable Energy System (HRES) through the integration of Solar Power Plants (PLTS) and Wind Power Plants (PLTB). The research method includes literature study, solar irradiation and wind speed data collection, HRES system design, and system performance analysis. The proposed system consists of a 300 Wp monocrystalline solar panel, a 300 W wind turbine, a 12 VDC 60 A hybrid MPPT controller, and a 4 × 20 Ah battery storage system. Solar irradiation data were obtained from Global Solar Atlas, while wind speed data were collected using Windy.com. The results show that the annual electrical energy production potential of the PLTS reached 1,381.2 kWh/year, with the highest production of 128.9 kWh occurring in August. Wind speed at the research location ranged from 1.54 to 4.11 m/s. The integration of PLTS and PLTB generated a maximum output power of more than 550 W and improved the stability and continuity of electricity supply. Therefore, the HRES system has strong potential as a sustainable energy solution for off-grid areas in Indonesia.